Oxford Research Encyclopedia of Global Public Health 2021
DOI: 10.1093/acrefore/9780190632366.013.307
|View full text |Cite
|
Sign up to set email alerts
|

Drowning: Global Burden, Risk Factors, and Prevention Strategies

Abstract: Drowning has been described as a major global public health problem and has recently been acknowledged by a United Nations Declaration on Global Drowning Prevention. While drowning impacts countries of all income levels, the burden is overwhelmingly borne by low- and middle-income countries (LMICs) who account for 90% of the global death toll. In addition, there is scarce data collection on drowning in LMICs, so the magnitude of drowning may be far greater than is represented. A range of factors including sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This may explain why the information provided on child drowning was generally sound but limited to risk reduction measures in a high income and domestic context. This finding strengthens calls for further research on child drowning in low-and middle-income countries and on open water drowning risk (Rahman et al, 2023). The drowning prevention community must also improve recognition of drowning as a risk during times of flood, particularly for children and in the context of a changing climate (Peden and Franklin, 2019).…”
Section: Policy and Practice Implicationssupporting
confidence: 60%
See 1 more Smart Citation
“…This may explain why the information provided on child drowning was generally sound but limited to risk reduction measures in a high income and domestic context. This finding strengthens calls for further research on child drowning in low-and middle-income countries and on open water drowning risk (Rahman et al, 2023). The drowning prevention community must also improve recognition of drowning as a risk during times of flood, particularly for children and in the context of a changing climate (Peden and Franklin, 2019).…”
Section: Policy and Practice Implicationssupporting
confidence: 60%
“…This likely reflects the high-income bias in the literature on child drowning that ChatGPT has at its disposal to formulate responses from. This adds further weight to the pre-existing call for further drowning prevention research from low-and middle-income countries (Rahman et al, 2023).…”
Section: Drowning Prevention: Drowning Risk In Childrenmentioning
confidence: 98%
“…However, most of previous evidence focused on fatal drowning, and research on non-fatal drowning was scarce and it was also unknown on the contribution of social determinants to the reduction of global drowning burden. 16 17 WHO and several studies reported that this reduction might be related to rapid improvement in social determinants of health (SDH) such as income, educational attainment and living environment. 4 10 17–19 For instance, Nguyen et al 10 found that low socioeconomic status or low-income households were associated with increased drowning mortality, but this study only investigated the impact of a single SDH on the burden of drowning at family level.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of previous evidence focused on fatal drowning, and research on non-fatal drowning was scarce and it was also unknown on the contribution of social determinants to the reduction of global drowning burden 16 17. WHO and several studies reported that this reduction might be related to rapid improvement in social determinants of health (SDH) such as income, educational attainment and living environment 4 10 17–19.…”
Section: Introductionmentioning
confidence: 99%
“…Swimming skills are an evidence-based component of drowning prevention 1. In Australia, children are expected to achieve the fundamental stage milestones of the National Swimming and Water Safety Benchmark by the age of 6 years 2.…”
Section: Introductionmentioning
confidence: 99%